Indication of Source - The Protection of Tenun Ikat Sumba to Encourage The Economy of The Local Community - Helitha Novianty Muchtar; Purnama Trisnamasyah (Jurnal Dinamika Hukum, 2019)
Tenun ikat Sumba is one craft of the Nusa Tenggara community used in worship services. The use of natural dyes in tenun ikat Sumba is an economic commodity that should be empowered to increase the economy of the Sumba community. The economic improvement of tenun ikat Sumba begins with an indication of source protection which should be given by the local government of Nusa Tenggara. This is a descriptive analytical study on the need of the local government to enforce the protection of tenun ikat Sumba through the inclusion of tenun ikat Sumba in a local government decree as a declarative effort in line with the mandate of Article 63 of Law Number 20 Year 2016 on Marks and Geographical Indications. Protection of indications of source by the local government is expected to encourage the economic progress of the local community, especially Sumba women, as well as the preservation of the culture of the local Sumba community.Keywords : Indication of source, tenun ikat Sumba, local community